Low-voltage current differencing buffered amplifier using only NMOS transistors - Dumawipata, Teerasilapa; Tangsrirat, Worapong; Surakampontorn, Wanlop (My University, 2007)
A circuit realization of a current differencing buffered amplifier (CDBA) in low-voltage operation is presented. The scheme is through the modification of a low-input resistance CCII+ and the proposed CDBA can operate with the minimum supply voltage of ±1.25V. In order that the signal path consists of only NMOS transistors, a negative current mirror using NMOS transistors is employed. With standard 0.5-gμm CMOS process parameters, PSPICE simulation results show that the proposed CDBA provides the terminal resistances of r n≅rp≅rw≅13 Ω, r z≅290 kΩ, and f-3dB ≅500 MHz. © 2007 IEEE.